Festival Grito Rock em Cuiabá (MT) : entre o underground e o mainstream - Vieira, Luiz Guilherme Santos (2022)
The scenario where this research is developed is the tricentennial capital of Mato Grosso (Cuiabá), in which the soundscape defined by Schafer (2001) is composed, above all, of rhythms of popular appeal, such as rasqueado, lambadão and sertanejo, but which is also — perhaps paradoxically — the birthplace of the Grito Rock festival, an initiative by Espaço Cubo that emerged in 2003. , independent and that approaches, in some way, the underground style (a concept understood here as something that is below the line of the underground) appropriates strategies of mainstream communication, not only to survive, but to grow exponentially. Thus, the general objective of the research is to analyze the relationship of the Grito Rock festival with the concept of underground coming from Gomes (2018) and to verify whether, in contemporary times, the referred event follows below the line of the underground or has already ascended to the scope of the mainstream. With an interdisciplinary approach, the research makes use of the case study methodology, to collect data, resorted to netnography, since, according to its creator Robert Kozinetts (2010), it is adapted to the complexities of our contemporary social world, mediated by technology.This study is justified, insofar as one perceives the economy of academic studies that evidence the festival that marked an entire generation, either agreeing or disagreeing with the forms of action used by the festival organizers and even started, later on, the collective Mídia Ninja, a new way of doing journalism, but which will not be covered in depth here, as it is not the focus of the study. The results indicate that the studied movement had an ascending curve between the period of 2003 and 2014, regarding the proportion and the local, national and world reach, presenting relevant aspects that insert it in the underground context with peculiar characteristics and close to minimalism, a concept with which is established a brief dialogue. Thus, it was concluded that, from the interweaving of knowledge produced, in view of future perspectives, the Grito Rock festival not only permeated the underground movement, but was also characterized as a form of resistance and redefinition of meanings in the cultural and artistic sphere.